Relationship between Co-Parenting and Communication with Marital Satisfaction among Married Couples with Teenagers - Felicia Musidora Khorlina; Jenny Lukito Setiawan (Universitas Ciputra Surabaya, 2017)
One of the reason couples get married are to start a family and have children. The presence of a child either brings happiness or can lead to a negative impact on the parent‟s relationship. The aim of this study is to examine the relationship between co-parenting and communication, together and partially with marital satisfaction among married couples with teenagers. The subjects (N=67) were either husbands or wives who have one or more teenage child. Subject consists of 32,8% husbands and 67,2% wives. The data was collected using the adaptation scale from Cordova (2009), an adaptation scale from PREPARE / Enrich (Olson & Larson, 2008), and an adaptation scale from Kansas Marital Satisfaction (Grable & Britt, 2006). Results showed that there is a significant positive relationship between co-parenting and communication together with marital satisfaction (R = 0.63; ρ <0.05). The results of partial correlation between co-parenting and marital satisfaction by controlling communication showed no correlation (r = 0.09; ρ > 0.05). Meanwhile, the results of the partial correlation between communication and marital satisfaction by controlling the co-parenting showed a significant positive correlation (r = 0.5; ρ <. 0.05). Based on these results, it could be concluded that co-parenting and communication indicates that there is a strong positive relationship with marital satisfaction among married couples with teenagers.